A collaborative study to establish the 1st WHO International Standard for human cytomegalovirus for nucleic acid amplification technology. Issue 4 (July 2016) - ,; Kessler, Harald; Rawlinson, William; Boivin, Guy; Preiksaitis, Jutta; Pang, Xiao-Li; Barranger, Côme; Alain, Sophie; Bressollette-Bodin, Céline; Hamprecht, Klaus; Grewing, Thomas; Constantoulakis, Pantelis; et al.
Abstract: Variability in the performance of nucleic acid amplification technology (NAT)-based assays presents a significant problem in the diagnosis and management of human cytomegalovirus (HCMV) infections. Here we describe a collaborative study to evaluate the suitability of candidate reference materials to harmonize HCMV viral load measurements in a wide range of NAT assays. Candidate materials comprised lyophilized Merlin virus, liquid Merlin virus, liquid AD169 virus, and purified HCMV Merlin DNA cloned into a bacterial artificial chromosome. Variability in the laboratory mean HCMV concentrations determined for virus samples across the different assays was 2 log10 . Variability for the purified DNA sample was higher (>3 log10 ). The agreement between laboratories was markedly improved when the potencies of the liquid virus samples were expressed relative to the lyophilized virus candidate. In contrast, the agreement between laboratories for the purified DNA sample was not improved. Results indicated the suitability of the lyophilized Merlin virus preparation as the 1st WHO International Standard for HCMV for NAT. It was established in October 2010, with an assigned potency of 5 × 10 6 International Units (IU) (NIBSC code 09/162). It is intended to be used to calibrate secondary references, used in HCMV NAT assays, in IU.